Beyond Barriers: Addressing Challenges and Opportunities of People with Disability During the Pandemic - Sumit Aggarwal; Heena Tabassum; Pragati Agarwal; Ashoo Grover; Ravinder Singh (Wolters Kluwer Medknow Publications, 2024)
People with disabilities often experience worse health outcomes than ordinary people because of multiple barriers to accessing healthcare. These inequalities are particularly exposed during the pandemic, indicating an urgent need to strengthen health systems, so that they are inclusive and responsive to the needs of these people during crises. These people are particularly affected by changes in routine services because of diversion of healthcare staff and facilities to respond to the pandemic, e.g., rehabilitation and medications. The combination of these factors substantially imparts negative impacts on their functioning and well-being. Health services research can help address the challenges of maintaining continuity of care during crises as well as addressing systematic inequalities in the health sector that marginalize people with disabilities even during noncrisis times. Therefore, research is needed to understand the health service design and to identify strategies to maximize active participation from this population.